A bZIP transcription factor VabZIP12 from blueberry induced by dark septate endocyte improving the salt tolerance of transgenic Arabidopsis. (February 2022) - Qu, Dehui; Wu, Fanlin; Zhao, Xiaohui; Zhu, Dongzi; Gu, Liang; Yang, Lina; Zhao, Weiwei; Sun, Yadong; Yang, Jingjing; Tian, Wei; Su, Hongyan; Wang, Lei
Highlights: Blueberry seedlings inoculated with DSE strain T010 grew more vigorously than the non-inoculated control under salt stress. A novel bZIP TFs VabZIP12 was highly up-regulated with T010 inoculation under salt stress. Overexpression of VabZIP12 enhanced salt stress tolerance in the transgenic Arabidopsis with up-regulation the related genes. Abstract: Dark septate endophytes (DSEs) have attracted much attention due to their positive roles in plant growth as well as resistance to various abiotic stresses. However, there are no reports on the molecular mechanisms of DSE fungi to improve salt tolerance in plants. In this study, the blueberry seedlings inoculated with T010, a beneficial DSE fungus reported previously, grew more vigorously than the non-inoculated control under salt stress. Physiological indicators showed that T010 inoculation increased antioxidant activities of blueberry roots. To explore its molecular mechanism, we focused on the bZIP TFs VabZIP12, who was highly up-regulated with T010 inoculation under salt stress. Further studies showed that VabZIP12, as a transcription activator, could combine both G-Box 1 and G-Box 2 motifs. Moreover, overexpression of VabZIP12 enhanced salt stress tolerance through increasing the activities of the enzymatic antioxidants in the transgenic Arabidopsis with up-regulation the related genes. These results indicated that the induction of VabZIP12 contribute to improving the tolerance of blueberry to salt stress by T010 inoculation.